Konsep Ideal Perlindungan Hukum terhadap Perempuan dan Anak Disabilitas Korban Kekerasan Seksual - Yuliana; Hertini, Mega Fitri; Ichsani, Immada; Mukti, Plasma Versiana (AL-SULTHANIYAH, 2025)
Cases of sexual violence against women and children with disabilities in West Kalimantan fluctuate annually, with a higher level of vulnerability compared to non-disabled groups. This situation emphasizes the need for more specific and equitable legal protection for disabled groups. This study aims to analyze the forms of legal protection for women and children with disabilities who are victims of sexual violence in West Kalimantan and to propose an ideal concept of legal protection that is inclusive and victim-centered. The method used is a normative-empirical approach through literature review and field research through interviews with several relevant parties. The results of the study indicate that although legal instruments are available, such as Law Number 8 of 2016 concerning Persons with Disabilities, Law Number 12 of 2022 concerning Criminal Acts of Sexual Violence, and Government Regulation Number 39 of 2020, their implementation is still suboptimal. Obstacles faced include limited access to information, communication barriers, social stigma, a lack of understanding among law enforcement officers regarding the special needs of persons with disabilities, and the absence of internal regulations at the police level regarding mechanisms for handling victims of disabilities. The ideal concept of legal protection encompasses three aspects: first, the provision of inclusive and accessible sexual education for women and children with disabilities; second, strengthening the capacity of law enforcement officers from a disability perspective; and third, the establishment of internal regulations or Standard Operating Procedures for handling victims of disabilities at the police level to ensure that examination standards for persons with disabilities are tailored to their needs.